C5a/C5aR regulates Th1/Th2 imbalance in sepsis-associated lung injury by promoting neutrophil activation to increase PAD4 expression - Zhenbing Lu; Ling Zhu; Changlin Yi; Bi Su; Renying Wang (Annals of Medicine)
Objective Multi-organ failure frequently complicates sepsis, with lungs being the primary target. T helper (Th) cell activation and phenotypic imbalance among them contribute significantly to sepsis-associated lung injury. Additionally, the complement system could regulate the polarized phenotype of T lymphocytes. Therefore, this study investigated the effect of C5a/C5a receptor (C5aR)/Peptidylarginine deiminase 4 (PAD4) on the Th1/Th2 ratio in sepsis-induced lung injury.Methods ELISA was used to detect the expression of PAD4, HBP, MPO, IL-1β, IL-10, IL-6, IL-4, syndecan-1, endocan and H3Cit. An LPS-induced septic lung injury mouse model was constructed, with HE and PAS stains evaluating lung damage. BCA kit quantified BALF total protein, Western blot examined C5aR, syndecan-1, endocan, PAD4 levels, while TUNEL and flow cytometry assessed tissue cellular apoptosis. Furthermore, flow cytometry was used to detect the +Th1 and Th2 cells proportion in peripheral blood, and CCK-8 was used to detect BEAS-2B activity.Results The results indicated that PAD4 and inflammatory factors were increased in lesion samples compared with controls. In sepsis-induced lung injury mice, addition of GSK484, a PAD4 inhibitor, effectively alleviated sepsis-induced lung edema and inflammatory responses. GSK484 was found to inhibit C5a/C5aR expression and suppress apoptosis and lung injury. Furthermore, GSK484 markedly inhibited Th1 cell phenotypes in vitro. Additionally, GSK484 intervention on Th1 cell phenotype further affected lung epithelial cell injury.Conclusion In summary, we revealed the mechanism of C5a/C5aR-induced PAD4 upregulation via neutrophil activation in sepsis-associated lung injury, causing a Th1/Th2 imbalance and lung injury, providing a novel approach for sepsis-associated lung injuries treatment.